2021
DOI: 10.1111/jcal.12571
|View full text |Cite
|
Sign up to set email alerts
|

Learning about a serious disease: When a personalized message is harmful unless you are happy

Abstract: According to the personalization principle, addressing learners by means of a personalized compared to a nonpersonalized message can foster learning. Interestingly, though, a recent study found that the personalization principle can invert for aversive contents. The present study investigated whether the negative effect of a personalized message for an aversive content can be compensated when learners are in a happy mood. It was hypothesized that the negative effect of a personalized compared to a nonpersonali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Therefore, both neutral and positive self‐referential materials are more likely to match the present self‐schema, leading to improved learning processes and outcomes. However, certain learning materials in education, such as knowledge about severe diseases, may be disregarded as they are less likely to align with the present self‐schema, resulting in limited learning improvement (Kühl & Münzer, 2021; Kühl & Zander, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, both neutral and positive self‐referential materials are more likely to match the present self‐schema, leading to improved learning processes and outcomes. However, certain learning materials in education, such as knowledge about severe diseases, may be disregarded as they are less likely to align with the present self‐schema, resulting in limited learning improvement (Kühl & Münzer, 2021; Kühl & Zander, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrate the potential utility of incorporating the self in educational contexts. Meanwhile, several researchers, such as Kühl and Münzer (2021) and Sinatra et al (2016), have encountered contradictory results. Interestingly, the findings from these studies even suggest an inverted self‐referencing effect for learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, based upon the CATLM, research about the influence of emotions and emotional states as well as motivation on multimedia learning has become a topic of major interest – with equivocal research findings (e.g., Um et al, 2012 ; Navratil et al, 2018 ; Kühl et al, 2019 ; Münchow and Bannert, 2019 ; Navratil and Kühl, 2019 ; Kühl and Münzer, 2021 ; Plass and Hovey, 2022 ; for meta-analyses see Brom et al, 2018 ; Wong and Adesope, 2020 ). For instance, results of an influential study by Um et al (2012) showed that learners’ positive emotional state and meaningful learning have a positive relation.…”
Section: Introductionmentioning
confidence: 99%